Diagnosis and Successful Surgical Treatment of Ascending Aorta Valved Conduit Rupture - М. V. Malakhova; Е. А. Prokhorova; А. S. Kulichkin; К. R. Bril’; Е. Yu. Van; А. N. Dzeranova; Т. N. Galyan; V. V. Khovrin; E. R. Charchyan (Вестник рентгенологии и радиологии)
Prosthetic infection is the most common complication after aortic replacement with a synthetic vascular prosthesis or a valved conduit (VC); in this case, aortic valve (AV) rupture occurs in 0.1-1.3% of patients. The cause of valve rupture is not only infective endocarditis; ascending aortic aneurysm and obvious calcification of the native AV are also known risk factors. The paper describes a clinical case of a 49-year-old patient examined and treated in Petrovsky Russian Scientific Center of Surgery. Eighteen years after primary surgical intervention for aortic stenosis, AV reprosthesis and ascending aorta VC replacement were performed according to the Bentall - De Bono procedure modified by Kouchoukos. In 2021, computed tomographic aortography has revealed that in the presence of infective endocarditis, there is aortic prosthetic rupture to form a paraprosthetic fistula and a pseudoaneurysm cavity. The results of instrumental studies are comparable with intraoperative data. The clinical case is of interest due to the rare occurrence of complications and to the significant role of multislice computed tomography during examination and postoperative monitoring.